Influence of Polyaniline Synthesis Conditions on its Capability for Removal and Recovery of Chromium from Aqueous Solution - Majid Riahi Samani (Iranian Journal of Chemistry & Chemical Engineering, 2011)
Absorptive characteristics of polyaniline synthesized in different solvents were studied. Water and mixture of water with other solvents were implemented for polyaniline synthesis. Synthesized polyanilines in powder shape is used as an adsorbent to remove toxic hexavalent chromium from aqueous solutions. Experiments were conducted in batch mode. Removal mechanism involving polyaniline is the combination of surface adsorption and reduction. The kind of solvent used at synthesizing stage can affect the capacity of produced polyanilines for removal of heavy metals including chromium. Synthesized polyaniline in water had the maximum chromium removal efficiency. The morphology study of polyanilines show that the type of solvent used for polymer synthesis affect the morphology of polyaniline.